2020
DOI: 10.1002/sctm.20-0314
|View full text |Cite
|
Sign up to set email alerts
|

Window of opportunity for human amnion epithelial stem cells to attenuate astrogliosis after umbilical cord occlusion in preterm fetal sheep

Abstract: There is increasing evidence that administration of many types of stem cell, including human amnion epithelial cells (hAECs), can reduce hypoxic-ischemic injury, including in the perinatal brain. However, the therapeutic window for single dose treatment is not known. We compared the effects of early and delayed intracerebroventricular administration of hAECs in fetal sheep at 0.7 gestation on brain injury induced by 25 minutes of complete umbilical cord occlusion (UCO) or sham occlusion. Fetuses received eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The lack of any neuroprotective or anti-inflammatory effects in this study is surprising. We have previously shown that a single intracerebroventricular bolus of 1 × 10 6 hAECs administered either 2 or 24 h after asphyxia induced by complete umbilical cord occlusion in preterm fetal sheep significantly improved neuronal survival in the hippocampus, partially improved myelination and was profoundly anti-inflammatory, attenuating the increase in microglia in both white and grey matter [ 16 ]. However, neither protocol improved recovery of EEG power or oligodendrocyte survival and only treatment started at 24 h, but not 2 h, improved neuronal survival in the striatum and thalamus., Furthermore, we have also previously shown that delayed intranasal infusion of 40.7 × 10 6 hAECS given on days one, 3 and 10 after 25 min of complete umbilical cord occlusion was associated with restored oligodendrocyte maturation and myelination as well as reduced inflammation as seen by a reduction in microglial and astrocyte numbers and attenuation of neuronal loss in the striatum but no improvement in the recovery of EEG power over 21 days of recovery in preterm fetal sheep [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of any neuroprotective or anti-inflammatory effects in this study is surprising. We have previously shown that a single intracerebroventricular bolus of 1 × 10 6 hAECs administered either 2 or 24 h after asphyxia induced by complete umbilical cord occlusion in preterm fetal sheep significantly improved neuronal survival in the hippocampus, partially improved myelination and was profoundly anti-inflammatory, attenuating the increase in microglia in both white and grey matter [ 16 ]. However, neither protocol improved recovery of EEG power or oligodendrocyte survival and only treatment started at 24 h, but not 2 h, improved neuronal survival in the striatum and thalamus., Furthermore, we have also previously shown that delayed intranasal infusion of 40.7 × 10 6 hAECS given on days one, 3 and 10 after 25 min of complete umbilical cord occlusion was associated with restored oligodendrocyte maturation and myelination as well as reduced inflammation as seen by a reduction in microglial and astrocyte numbers and attenuation of neuronal loss in the striatum but no improvement in the recovery of EEG power over 21 days of recovery in preterm fetal sheep [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, it is not clear how the route of administration would affect the number of hAECs that reached the brain and their efficacy. The current study is one of the first studies of perinatal brain injury to give hAECs intravenously rather than intracerebroventricularly or intranasally [ 16 , 17 ]. Interestingly, in a study in newborn piglets after hypoxia ischemia, intranasal administration of mesenchymal stromal cells was associated with modest augmentation of hypothermic neuroprotection, including better recovery of amplitude integrated EEG and increased oligodendrocyte number in the hippocampus, internal capsule and periventricular white matter compared with when cells were administered intravenously [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed intranasal infusion of hAECs, given at 24 h and 3 and 10 days after 25 min of complete umbilical cord occlusion, was associated with improved brain weight, improved oligodendrocyte maturation and myelination and reduced microglia and astrocyte number after 21 days recovery in the preterm fetal sheep [ 186 ]. Further, hAECS have a relatively long therapeutic window of opportunity, showing similar anti-inflammatory effects when administered either 2 or 24 h after 25 min of complete umbilical cord occlusion in the preterm fetal sheep [ 187 ]. By contrast, hAECs did not reduce markers of neuroinflammation and injury in preterm lamb brains after mechanical ventilation; however, this was assessed at 48 h after birth and this may be too short a recovery period to see an effect [ 188 ].…”
Section: Potential Neuroprotective Treatments Showing Promise In Pmentioning
confidence: 99%
“… 59 Furthermore, treatment with human amnion epithelial cells could alleviate hypoxic‐ischemic injury in the perinatal brain. 60 Hypoxic preconditioning increased grafted‐cell survival of NSCs and improved therapeutic effects of NSC transplantation in a hemorrhagic stroke mouse model. 61 Finally, hypoxia‐preconditioned olfactory mucosa MSCs were shown to inhibit the death of microglia after cerebral ischemia/reperfusion insult via HIF‐1α activation.…”
Section: Hypoxia and Stem Cellsmentioning
confidence: 99%